BCG-loaded chitosan microparticles: interaction with macrophages and preliminary in vivo studies - Caetano, Liliana Aranha (2017)
The aim of this study was to develop a novel BCG-loaded chitosan vaccine with high association efficiency which can afford efficient interaction with APC and elicit local and Th1-type-specific immune response after intranasal administration. Chitosan-suspended BCG and BCG-loaded chitosan-alginate microparticles were prepared by ionotropic gelation. Interaction with APC was evaluated by fluorescence microscopy using rBCG-GFP. Specific immune responses were evaluated following intranasal immunisation of mice. Cellular uptake was approximately two-fold higher for chitosan-suspended BCG. A single dose of BCG-loaded microparticles or chitosan-suspended BCG by intranasal route improved Th1-type response compared with subcutaneous BCG. Chitosan-suspended BCG originated the highest mucosal response in the lungs by intranasal route. These positive results indicate that the proposed approach of whole live BCG microencapsulation in chitosan-alginate for intranasal immunisation was successful in allowing efficient interaction with APC, while improving the cellular immune response, which is of interest for local immunisation against tuberculosis.